Ultrasonographic characteristics of medullary thyroid carcinoma according to nodule size: application of the Korean Thyroid Imaging Reporting and Data System and American Thyroid Association guidelines. (April 2021) - Hahn, Soo Yeon; Shin, Jung Hee; Oh, Young Lyun; Park, Ko Woon
Background: Few studies have categorized ultrasound (US) findings of various sized medullary thyroid carcinomas (MTCs) according to updated guidelines. Purpose: To evaluate and compare the differences in US findings of MTC according to nodule size, using the Korean Thyroid Imaging Reporting and Data System (K-TIRADS) and American Thyroid Association (ATA) guidelines. Material and Methods: The study included 119 patients with 129 MTC nodules, which were surgically confirmed at our institution between March 1999 and September 2017. Nodules were divided into large (≥1.0 cm) and small (<1.0 cm) groups. US images were analyzed according to the K-TIRADS and ATA guidelines. The differences in US characteristics between small and large nodules were compared using Fisher's exact or Chi-square tests. Results: Of 129 MTC nodules, 84 (65.1%) were large nodules and 45 (34.9%) were small nodules. According to the nodule size, small MTC nodules were classified more commonly as high suspicion by K-TIRADS and ATA (95.6% and 93.3%, respectively) ( P  < 0.001), but presented neither cystic change, isoechogenicity, nor low suspicion category by K-TIRADS and ATA. In contrast, large MTC nodules showed more frequently cystic change (15.5%), isoechogenicity (16.7%), smooth margins (50%), or low or intermediate suspicion US features by K-TIRADS and ATA (59.6% and 36.0%, respectively) (all P values < 0.001). Conclusion: Most small MTC nodules are classified as high suspicion on US, whereas large MTC nodules are diagnosed more frequently as low or intermediate suspicion by K-TIRADS and ATA.